Expression and functional analyses of Krüppel-like factor 3 in chicken adipose tissue. Issue 4 (3rd April 2014) - Zhang, Zhi-Wei; Wu, Chun-Yan; Li, Hui; Wang, Ning
Abstract: Studies in mammalian species showed that Krüppel-like factor 3 (KLF3) regulated adipose tissue development. However, it was not reported in chicken. In the current study, we found that during the growth and development of abdominal fat tissue, chicken KLF3 ( Gallus gallus KLF3, gKLF3 ) was consecutively expressed, and its transcripts were higher at 7 weeks of age and lower at 10 weeks of age in lean broilers than in fat broilers. In addition, gKLF3 overexpression suppressed chicken CCAAT/enhancer binding protein alpha ( C/EBPα ), fatty acid binding protein 4 ( FABP4 ), fatty acid synthase ( FASN ), and lipoprotein lipase ( LPL ) promoter activities, but increased chicken peroxisome proliferator-activated receptor gamma ( PPARγ ) promoter activity. Additionally, point mutagenesis analysis showed that the substitution of Asp by Gly within the Pro-Val-Asp-Leu-Thr (PVDLT) motif of gKLF3 significantly reduced the ability of gKLF3 to regulate the promoter activities of FABP4, FASN, LPL, C/EBPα, and PPARγ . Graphical abstract: : Effects of Overexpression of KLF3 and Its Mutant on the Promoter Activities of Chicken FABP4, FASN, LPL, C/EBPα, and PPARγ in DF1 Cells.